2016
DOI: 10.3390/ijms17091388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormone Therapy on Oxidative Stress in Postmenopausal Women with Metabolic Syndrome

Abstract: The aim of this study was to determine the effect of oral hormone therapy (HT) on oxidative stress (OS) in postmenopausal women with metabolic syndrome (MetS). A randomized, double blind, placebo-controlled trial was carried out. We formed four groups of 25 women each; healthy (HW) and MetS women (MSW) were assigned to HT (1 mg/day of estradiol valerate plus 5 mg/10 day of medroxiprogesterone) or placebo. We measured plasma lipoperoxides, erythrocyte superoxide dismutase and glutathione peroxidase, total plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
1
10
1
1
Order By: Relevance
“…Likewise, a cross-sectional study from Japan with 100 on average 59-year-old patients with type 2 diabetes observed significantly higher D-ROM levels in women than men 27. A hormone replacement therapy (HRT) may be considered after a thorough risk-benefit evaluation for each individual perimenopausal or postmenopausal woman with T2DM who is experiencing high OS because there is evidence from many clinical trials that HRT is effective in lowering various OS biomarkers 28–30…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a cross-sectional study from Japan with 100 on average 59-year-old patients with type 2 diabetes observed significantly higher D-ROM levels in women than men 27. A hormone replacement therapy (HRT) may be considered after a thorough risk-benefit evaluation for each individual perimenopausal or postmenopausal woman with T2DM who is experiencing high OS because there is evidence from many clinical trials that HRT is effective in lowering various OS biomarkers 28–30…”
Section: Discussionmentioning
confidence: 99%
“… 56 Hormone therapy improves the lipid and oxidative alterations that occur in MetS in post-menopausal women. 57 Cumulative alcohol consumption may be an especially important confounding factor. Our previous study found that an ‘alcohol’ dietary pattern was present in Chinese men.…”
Section: Discussionmentioning
confidence: 99%
“…2 Oxidative stress increases in postmenopausal females. 3 This is because of decreasing levels of estrogens as it acts as direct scavenger of free radicals. 4 The increased oxidative stress in postmenopausal females results in heart diseases, vasomotor disturbances and osteoporosis.…”
Section: Introductionmentioning
confidence: 99%